Colombia : Land Policy in Transition - Deininger, Klaus (World Bank, Washington, DC, 2012)
Only 30 percent of land suitable for agriculture is utilized for crops (with significant regional variation). More than double the area suitable for pasture is used for livestock grazing, with negative environmental consequences. Although markets provide land access to poor and productive producers, they are not effective in transferring land from large to small producers, implying continuing concentration, driven largely by violence and displacement. Data from about 800 municipalities show that high land inequality is associated with greater expansion of livestock farming into ecologically fragile areas unsuitable for farming, and underutilization of agricultural land. This inhibits Colombia from realizing its comparative advantage in perennials and high-value-added crops, and reduces the agricultural sector's contribution to economic growth.